PELANGGARAN ADMINISTRASI DALAM PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR, BUPATI DAN WAKIL BUPATI, SERTA WALIKOTA DAN WAKIL WALIKOTA TAHUN 2020 - Budiman NPD Sinaga; Johnson Pasaribu; Jherry Napitupulu (Visi Sosial Humaniora, 2021)
In the Constitution of the Republic of Indonesia 1945 it was stated that the election of regional heads was conducted democratically. As the implementation of the provision has been applied various laws and regulations but until now there are still various problems. Therefore, it is necessary to conduct research on the problems in the regional head election. Research was conducted on legislation and decisions. Based on the research can be known that in the Regional Head Election found also administrative violations. In resolving administrative violations, the role of administrative science is very important especially regarding evidence and evidence. Therefore, election organizers need to be equipped with administrative capabilities in order to prevent and resolve violations appropriately.